Linguistic Diversity in Education: Strategies for Inclusive Learning Environments - Wijayanti, Rani Amrista (English Education Department - Universitas Nasional Karangturi, 2024)
This research explores the intricate dynamics of linguistic diversity in junior high school education with the goal of shedding light on the experiences of students from diverse language origins. The study highlights the significance of acknowledging and valuing the different linguistic environments inside educational settings, as Bahasa Indonesia is predominantly used by 18 out of 30 students, alongside other languages such as Lampungnese and Javanese. The investigation on communication comfort uncovers that most students feel comfortable while using their native language but sometimes experience discomfort during intricate talks, highlighting the need for customised teaching methods. The challenges encountered by students, such as comprehending instructions and experiencing emotions of exclusion, emphasise the practical and emotional aspects of language diversity, hence requiring comprehensive support solutions. The importance of diverse instructional techniques is emphasised by a preference for interactive teaching methods and visual aids. The importance of teacher assistance is highlighted, as students emphasise the need to acknowledge and appreciate linguistic variety while also suggesting the provision of customised materials. The curriculum should accurately reflect the diverse cultural context, requiring a fair and comprehensive approach. Students' proactive use of solutions to overcome linguistic challenges demonstrates their perseverance and ingenuity. Ultimately, this research supports the implementation of inclusive strategies that recognise and address the unique requirements of linguistically varied junior high school children. It aims to create settings that embrace and appreciate linguistic variety